2016
DOI: 10.1155/2016/9312340
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review of the Literature on Existing Punctal Plugs for the Management of Dry Eye Disease

Abstract: Numerous designs of punctal and canalicular plugs are available on the market. This variety presents challenges to ophthalmologists when choosing punctal plugs for the management of various ocular conditions. The aim of this literature review is to provide a classification system for lacrimal occlusive devices based on their location and duration of action as well as to identify different characteristics of each one of them. We want to give a comprehensive overview on punctal and canalicular plugs including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 83 publications
0
35
0
2
Order By: Relevance
“…Marcet et al summarised the evidence from 21 case series and six randomised trials 40. Jehangir et al provided a review of the available punctal plug materials, designs and uses, as well as the complications associated with punctal plug treatment 41. All authors concluded that punctal plugs are an effective and relatively safe means for treating dry eye.…”
Section: Discussionmentioning
confidence: 99%
“…Marcet et al summarised the evidence from 21 case series and six randomised trials 40. Jehangir et al provided a review of the available punctal plug materials, designs and uses, as well as the complications associated with punctal plug treatment 41. All authors concluded that punctal plugs are an effective and relatively safe means for treating dry eye.…”
Section: Discussionmentioning
confidence: 99%
“…[95] Plugs (Figure 2) are classified by the location of insertion, which can include either the puncta or canaliculi (nasolacrimal drainage ducts) and plugs can be either permanently or temporarily inserted. [96] A factor that contributes to the intended duration of usage is the composition of the tear plug, which could be made of degradable collagen, gelatin, as well as non-degradable materials such as silicone, Teflon, and hydromethylacrylate. [95] Even though tear plugs are considered safe and have shown to be effective for maintaining ocular lubrication, some individuals experience complications associated with plug retention rates and infection.…”
Section: Ocular Diseasesmentioning
confidence: 99%
“…[95] It also has been demonstrated that closing the puncta exposes the ocular surface to high levels of pro-inflammatory cytokines in the tears, which can lead to exacerbated symptoms of DED. [96] …”
Section: Ocular Diseasesmentioning
confidence: 99%
“…Preservative-free artificial tears are preferable for long-term use because preserved formulations may be toxic to the cornea and conjunctival epithelium (Lemp 1994; Pflugfelder 2000; Pucker 2016). Interventions such as bandage contact lenses (physical coverage of the ocular surface), estrogens (hormone replacement), topical corticosteroids (general im-munosuppressant), cyclosporine (immunosuppressant agent that decreases T-cell production), pilocarpine (cholinergic parasympa-theticomimetic agonist), and punctal plugs (lacrimal drainage occlusion device) also have been shown to be effective treatments in selected settings (DEWS 2007a; Freeman 1975; Jehangir 2016 Lemp 1994; Pflugfelder 2000; Sall 2000; Sheppard 2003; Wilson 2003). …”
Section: Introductionmentioning
confidence: 99%
“…Thermal cautery or argon laser achieves permanent occlusion of the puncta (AAO 2003; Dohlman 1978; Lemp 1994). Similar to punctal occlusion, intracanalicular plugs also block tear drainage, though they act by blocking the canalicu-lus instead of the punctum (Jehangir 2016). …”
Section: Introductionmentioning
confidence: 99%